O pluralismo ontológico à luz da fenomenologia-hermenêutica - Dietrich, Gabriel Henrique (2023)
The main objective of this study is to present and justify hermeneutic pluralism. Broadly speaking, hermeneutic pluralism is presented as a meta-ontological position according to which there are multiple irreducible ways of being. More specifically, this presentation finds its lines of justification in Being and Time and in the phenomenology-hermeneutics elaborated there. In summary, from the perspective articulated here, Heidegger's commitment to hermeneutic pluralism implies that the elucidation of ontological diversity involves a critical return to the understanding of being. Thus, the understanding of being offers the initial basis of support for the thesis that there are multiple irreducible ways of being. Generally, ways of being are interpreted in this work as ontological standards that establish the identity of the entities under which they are comprehensively projected. More specifically, these patterns involve the articulation of a triad of ontological constraints that concern the specific ways in which entities are individuated, their respective ways of determination and their respective modes of phenomenalization and donation. In order to contextualize Heidegger's pluralist reception, the first chapter introduces the contemporary meta-ontological turn and the debate between monism and ontological pluralism, which in this context are both quantificational. Thus, initially the thesis of the variety of modes is presented in the context of the dispute between Peter van Inwagen's neo-Quinean monism and Kris McDaniel's quantificational pluralism. To the extent that this context includes the attribution to Heidegger of the commitment to pluralism, the way to justify this attribution is critically examined. This critical examination results in the recognition that the quantificational proposal is insufficient, as it does not grant due centrality and importance for the understanding of being. Precisely with a view to overcoming this difficulty, the second chapter presents the methodological contours that establish the supporting ballast and guiding horizon of the ontological program of Being and Time as a whole. With these methodological elements in hand, the final chapter consists of the presentation of three modes of being through which entities receive their respective ontological identities, the horizons of meaning within which they are accessible as such. Thus, the ways of being of subsistence (Vorhandenheit), availability (Zuhandenheit) and existence (Existenz) are presented based on the triad of ontological conditioning factors involved in the projective understanding that articulates entities in their respective horizons of meaning, that is, each mode of being belongs to a specific way in which the entity obtains its characteristic determinations, its ways of giving and phenomenalization, and, finally, its respective mode of individuation. The interpretative line adopted here also offers resources to elucidate the complex relationship between time and being, which, although expressly stated in the title, is not fully developed in Heidegger's body of work. In summary, the interpretative hypothesis that the pluralist line of reception offers is that each way of being corresponds to a specific temporal framework, that is, in the understanding of being there is a determined temporal framework. Considering that in Being and Time three concepts of time are recognized, namely, vulgar or common time, world time and original temporality, the interpretative hypothesis of this work seeks to demonstrate how the projective understanding of entities that subsist, are available or exist it takes root in each of these temporal frameworks. Ultimately, therefore, hermeneutic pluralism as presented in this study finds in temporality the ballast for inserting its lines of justification, seeking to do justice to the animating spirit of Being and Time.